IL-18BP is a secreted immune checkpoint and barrier to IL-18 immunotherapy - Zhou, Ting; Damsky, William; Weizman, Orr-El; McGeary, Meaghan K.; Hartmann, K. Patricia; Rosen, Connor E.; Fischer, Suzanne; Jackson, Ruaidhri; Flavell, Richard A.; Wang, Jun; Sanmamed, Miguel F.; Bosenberg, Marcus W.; et al. (Nature (London), 2020)
Cytokines were the first modern immunotherapies to produce durable responses in patients with advanced cancer, but they have only modest efficacy and limited tolerability 1 , 2 . In an effort to identify alternative cytokine pathways for immunotherapy, we found that components of the interleukin-18 (IL-18) pathway are upregulated on tumour-infiltrating lymphocytes, suggesting that IL-18 therapy could enhance anti-tumour immunity. However, recombinant IL-18 previously did not demonstrate efficacy in clinical trials 3 . Here we show that IL-18BP, a high-affinity IL-18 decoy receptor, is frequently upregulated in diverse human and mouse tumours and limits the anti-tumour activity of IL-18 in mice. Using directed evolution, we engineered a ‘decoy-resistant’ IL-18 (DR-18) that maintains signalling potential but is impervious to inhibition by IL-18BP. Unlike wild-type IL-18, DR-18 exerted potent anti-tumour effects in mouse tumour models by promoting the development of poly-functional effector CD8 + T cells, decreasing the prevalence of exhausted CD8 + T cells that express the transcriptional regulator of exhaustion TOX, and expanding the pool of stem-like TCF1 + precursor CD8 + T cells. DR-18 also enhanced the activity and maturation of natural killer cells to effectively treat anti-PD-1 resistant tumours that have lost surface expression of major histocompatibility complex class I molecules. These results highlight the potential of the IL-18 pathway for immunotherapeutic intervention and implicate IL-18BP as a major therapeutic barrier. An engineered version of IL-18 that is resistant to binding by the soluble decoy receptor IL-18BP shows strong anti-tumour activity in mouse models of cancer.